2005
DOI: 10.1029/2005gl024749
|View full text |Cite
|
Sign up to set email alerts
|

Westward shift of the Yellow Sea warm salty tongue

Abstract: [1] The accumulated in situ hydrographic survey as well as the satellite observed sea surface temperature (SST) show consistent westward shifting of the Yellow Sea Warm Salty Tongue (YSWST) in winter. A 2-D thermal model is used to show the westward shifting of the YSWST due to cooling and advection. The MITgcm is applied to simulate the circulation in the Yellow and East China Seas. Under the northern monsoon wind in winter, the sea surface height (SSH) is adjusted to have a ridge in the channel and a trough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 6 publications
1
36
0
Order By: Relevance
“…At the time of proofreading, it came to our attention that Huang et al [2005] has reached a similar conclusion based on theoretical and modeling results. The YSWC transports warm and saline water brought by the anticyclonic Cheju Warm Current (CWC) ] into the southwestern YS, which has a very important positive influence on temperature variation.…”
Section: Discussionmentioning
confidence: 83%
“…At the time of proofreading, it came to our attention that Huang et al [2005] has reached a similar conclusion based on theoretical and modeling results. The YSWC transports warm and saline water brought by the anticyclonic Cheju Warm Current (CWC) ] into the southwestern YS, which has a very important positive influence on temperature variation.…”
Section: Discussionmentioning
confidence: 83%
“…The COADS includes net heat flux (Q), shortwave radiation, surface freshwater flux, and wind stress. This data set has the advantage of having a relatively long reference period, which is important for the climatological mean, and has also been validated by modeling studies for the eastern Chinese seas (Huang et al, 2005;Zhou et al, 2009;Zhou et al, 2015). Thermal feedback was introduced to correct heat flux with bulk formulas (Marchesiello et al, 2001).…”
Section: Circulation Model and Forcingmentioning
confidence: 99%
“…5c). The cause of this shift has been discussed by previous authors (e.g., Tang et al, 2001;Huang et al, 2005), and is the subject of a separate study.…”
Section: Discussionmentioning
confidence: 88%
“…However, Riedlinger and Jacobs (2000) reported that the Kuroshio and the Taiwan Warm Current could intrude into the HS, advecting warm waters into the HS. Huang et al (2005) pointed out that both surface cooling and advection of the current play an important role in the formation of the tongue in the winter. Ma et al (2006) concluded that the bathymetric effect was a large contributor in forming the temperature gradient, while the HWC was also an important factor in determining the warm tongue's structure and position.…”
Section: Introductionmentioning
confidence: 99%